Edaphic factors, successional status and functional traits drive habitat associations of trees in naturally regenerating tropical dry forests. (8th October 2018) - Werden, Leland K.; Becknell, Justin M.; Powers, Jennifer S.
Abstract: Many studies have examined individual environmental drivers of tropical tree species distributions, but edaphic and successional gradients have not been considered simultaneously. Furthermore, determining how functional traits influence species distributions along these gradients may help to elucidate mechanisms behind community assembly. To assess the influence of environmental filtering on tropical dry forest (TDF) tree species distributions, we used forest inventory data from sites with large edaphic and successional gradients in NW Costa Rica. Our goals were to determine (1) whether edaphic or successional factors are more important determinants of the abundance of individual tree species in regenerating TDF, (2) how species‐level functional traits are related to edaphic and/or successional niche associations of tree species and (3) correlations between species‐level edaphic and successional niche associations. The distributions of 82 focal tree species were strongly driven by both edaphic and successional gradients. Overall, 94% of species responded to soil chemistry, 89% to soil texture and 94% to stand age gradients. Some functional traits were correlated with the edaphic and successional niche associations of TDF tree species. Species that specialized on soils with high total nutrient concentrations had higher foliar nutrient concentrations (nitrogen and phosphorus) and lower leaf dry matter content (LDMC). Species with wider stand age niches had lower LDMC and wood density. There were no correlations between edaphic and successional niche optima of TDF tree species. Our results indicate that successional and edaphic gradients concurrently drive community assembly in regenerating TDF. Moreover, our work underscores the importance of considering how the functional characteristics of TDF trees dictate species distributions across environmental gradients. Aplain language summary is available for this article. Abstract : Plain Language Summary